Analysis of problematic credit completion at Bank BNI 46 branch Polewali Mandar - Andi Aprasing; Ika Novitasari (Indonesia Prime, 2021)
Lending to banks generally aims to make a profit, and these results can be obtained in the form of interest received by the Bank in return for services and administrative costs. Credit charged to the customer. This profit is essential for the survival of the Bank. In addition, profits can also increase the Bank's business. The provision of credit carried out in BNI 46, between BNI 46 as a creditor and the customer as a debtor, is a form of channeling funds from the Bank to the community as a function of the Bank itself. In collecting funds from the district and distributing them to the community. This research is empirical normative research, so that field research and data accuracy are carried out with interviews to Bank BNI 46 and the public as recipients. Credit